New Experimental Correlations for the Mass Transfer of a High-efficiency Packed-type Dehumidifier - Wang Lingshi; Xiao Fu; Lu Tao (Zhileng xuebao)
The packing is a crucial part of a liquid-desiccant dehumidifier, and its mass-transfer characteristics have a great impact on the overall performance of liquid-desiccant-based air-conditioning systems. An experimental test rig was built to study the performance of a counter-flow packed-type liquid-desiccant dehumidifier that employs cross-corrugated cellulose-structured packing with a high specific surface area (650 m2/m3). A LiCl aqueous solution was used as the desiccant solution. The water-vapor pressure difference between the gas and liquid interface was considered as the mass-transfer-driven force. New experimental correlations for the mass-transfer coefficient and the dehumidification effectiveness were developed. The performance of this type of packing was compared with other types of packing in the literature. The results show that this type of packing has the highest volumetric mass-transfer coefficient. In addition, the volumetric mass-transfer coefficient is found to increase with the specific surface area of the packing. The deviations between the experimental data and the predicted data using the experimental correlation for the mass-transfer coefficient are within ±20%, and within ±15% for the dehumidification effectiveness. This indicates that the two new correlations can be used to accurately predict the mass-transfer performance of a dehumidifier.